Consortium of Candida utilis, Kluyveromyces marxianus and Saccharomyces cerevisiae Yeasts for Vinasse Fermentation of Agave americana L. Liquor for Biomass Production and Reduction in Chemical Oxygen Demand - Roberto Robles Calderón; Francisco Alcántara Boza; Elmer Benmites-Alfaro; Oscar Tinoco Gómez; Jaqueline Chirre Flores (Fermentation)
The vinasse from Agave americana L. (blue cabuya) liquor has a high concentration of organic matter, nutrients with high chemical oxygen demand (COD), and low pH, properties that give it the potential to generate adverse impact on the environment if improperly disposed of. In other countries, studies have been conducted on yeast strain combinations in vinasses to produce biomass and reduce organic load, but there are no studies of the aforementioned yeast consortium in blue cabuya liqueur vinasses to produce biomass and reduce COD. Given this problem, the objective of the research was to reduce this adverse environmental impact through aerobic fermentation of this vinasse with the yeast consortium Candida utilis, Kluyveromyces marxianus and Saccharomyces cerevisiae (D 47-Lalvin). As a result, biomass production and COD reduction were achieved. The study evaluated temperature variables of 28 °C, 30 °C, and 32 °C, and pH values of 3, 4, and 5 under conditions of consortium and nutrient diammonium phosphate (DAP) concentrations of 1.32 g/L and 1.5 g/L, respectively, in a bioreactor with automatic control of temperature, time, stirring speed of 100 RPM, and air flow of 1 VVM. The result was a biomass yield of 93.4% and a COD reduction of 33.3%. It is concluded that the aerobic fermentation process of blue cabuya liquor vinasse with the yeast consortium employed produces a high biomass yield, which can be used for its protein value as an animal feed supplement and, due to its low COD value, as an agricultural fertilizer.